Profile of tuberculosis cases in pernambuco: analysis of cases, 2011 to 2020 - de Lima Rodrigues Souza, Claudia; Ulysses Rodrigues de Souza, José; Vitória Alves Vila Nova , Maria; Fernanda Guedes, Brenda; Cristina Rozeno, Michelly; Rejane Florentino Soares, Daiany; Izabely Silva Pimentel, Maria (Seven Editora, 2023)
Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis hominis. In developing countries, such as Brazil, it remains a prevalent infectious disease. Tuberculosis is transmitted through the elimination of bacilli by the respiratory route and its infectivity is directly related to the immune status of the individual. The article aims to identify the profile of confirmed cases of tuberculosis in the period from 2011 to 2020 in Pernambuco. This is an observational, descriptive, quantitative and longitudinal field study, in a time frame from 2011 to 2020. Secondary data were collected from the website of the Department of Informatics of the Brazilian Unified Health System (Datasus), specifically from the Information System of Information on Diseases and Notification (SINAN). The variables were standardized through rates per 100 thousand, with the following variables: sex, race/color, age group, education, form, and closure, analyzed descriptively by means of absolute and relative values. According to the results observed in this research, the cases of tuberculosis mostly occur in mixed-race men, aged between 20 and 39 years, with a blank field of education (and followed by 1st to 4th grade of elementary school), presenting the pulmonary clinical form and with closure situation with cure achieved. DOI: 10.56238/pacfdnsv1-050